Characteristics of Personal Exposure to Polycyclic Aromatic Hydrocarbons in Public Transportation Environments in Beijing - Mei Zheng; Caiqing Yan; Qiaoyun Yang; Xinghua Qiu; Huaiyu Fu; Xiaoying Li; Zhu, Tong (Research of Environmental Sciences, 2014)
Characteristics and sources of particle-bound polycyclic aromatic hydrocarbons ( PAHs) in PM_(2. 5) in three typical transportation microenvironments were investigated,and the health risks were assessed. Fine particle exposure by pedestrians and commuters taking buses and subways were collected using personal exposure samplers in December 2011 in Beijing. Concentrations of multiple PAHs were measured by gas chromatography-mass spectrometry ( GC-MS) . Sources of PAHs were identified by distribution patterns and ratios of different PAHs. Health risk assessments associated with respiratory exposure to PAHs were conducted based on benzo[a]pyrene ( BaP) equivalent concentrations ( BEQ) ,BaP based equivalent carcinogenic power ( BaPE) and inhalation cancer risk. The results showed that: 1) The average exposure level of PAHs in roadside,buses,and subways were ( 120 119) ,( 101 46. 6) ,and ( 50. 8 25. 6) ng/m~3 , respectively. 2) The similarity of PAHs distribution patterns in the three transportation microenvironments and the ratios of PAHs rho( Flt) / [rho( Flt) + rho( Pyr) ]and rho( IcdP) /[rho( IcdP) + rho( BghiP) ]> 0. 5,rho( BaA) /[rho( BaA) + rho( Chr) ]> 0. 35 suggested common sources in these environments,mainly from vehicle emissions and coal combustion. 3 ) Inhalation cancer risk ( 19. 8 * 10 ~(- 6) , California Environmental Protection Agency( CalEPA) -based method; 15. 6 * 10~( - 4),World Health Organization ( WHO) -based method) was found to be highest in the roadside environment,about 1. 4 and 3. 6 times those for buses and subways,respectively. 4) PAHs were more enriched under the roadside and bus environments. Exposure to PAHs and the health risks obviously increased in the roadside environment during days with elevated PM_(2. 5) concentrations.对北京市3种典型交通环境下PM_(2.5)中PAHs(多环芳烃)的污染水平、来源及其暴露健康风险进行了研究.于2011年12月利用颗粒物个体暴露 采样器采集北京市道路边、公共汽车、地铁等不同交通环境下的PM_(2.5)样品,采用GC-MS测定rho(PAHs),结合PAHs组成特征以及特征 化合物比值等鉴别PAHs来源,根据苯并[a]芘等效毒性(BEQ)、等效致癌浓度(BaPE)及致癌风险等参数评估PAHs呼吸暴露的健康风险.结果显 示:1观测期间,北京市道路边、公共汽车和地铁内rho(PAHs)平均值分别为(120119)、(10146.6)、(50.825.6)ng/m~ 3;23种交通环境下PAHs特征成分谱相似,rho(荧蒽)/[rho(荧蒽)+rho(芘)]、rho(茚并[1,2,3-cd]芘)/[rho(茚 并[1,2,3-cd]芘)+rho(苯并[g,h,i]苝)]均大于0.5,rho(苯并[a]蒽)/[rho(苯并[a]蒽)+rho()]大于0. 35,表明机动车尾气和燃煤排放是北京冬季3种交通环境下PAHs的重要贡献源;3分别采用美国加州环境保护局(California Environment Protection Agency,CalEPA)和世界卫生组织(World Health Organization,WHO)方法计算致癌风险可知,2种方法计算的道路边PAHs的致癌风险(19.8*10~(-6)、15.6*10~(-4 ))最高,约为公共汽车及地铁内的1.4和3.6倍;4道路边与公共汽车内的PAHs在PM_(2.5)中更为富集,道路边PAHs污染水平及健康风险在 高rho(PM_(2.5))环境下增加显著.